Exploring the Feasibility of an Adapted Home-Based Video Exercise Program for Primary School-Aged Children in Malaysia: A Preliminary Investigation - Abdul Wahat, Nor Haniza; Khairol Anur, Nur Dini Izzati; Zanuddin, Nor Asfarina; Rantai, Vivian Sheereen Anak; Jamaluddin, Mohd Khairil Azahar (Seminars in Hearing, 2025)
Vestibular rehabilitation therapy (VRT) has demonstrated effectiveness in adults; however, evidence supporting its use in children remains limited. Given the potential developmental impacts of vestibular-related problems, it is essential to identify accessible and age-appropriate strategies for targeted rehabilitation in pediatric populations. In Malaysia, access to physical therapists trained in vestibular rehabilitation for children is limited, and logistical barriers often hinder regular clinic attendance. These challenges underscore the need for a home-based alternative.This study aimed to adapt and evaluate the feasibility of a home-based video exercise program (HBVEP) for children aged 7 to 12 years old.The structured feasibility questionnaire revealed strong parental endorsement, with most responses ranging from “agree” to “completely agree” regarding the exercise program's acceptability, appropriateness, and feasibility. Completion time data indicated that the exercises were manageable, and analysis of exercise preferences offered insight into which components were most engaging for children and parents.The results support the practicality of the HBVEP as a targeted rehabilitation approach for school-aged children. It offers a flexible, low-cost alternative to in-clinic therapy. However, further research involving children with vestibular and balance impairments is needed to assess the full clinical utility and effectiveness of this intervention.
Keywords: vestibular rehabilitation therapy; home-based exercise module; feasibility; children; pediatric audiology